Utopic dreams and apocalyptic fantasies : critical approaches to researching video game play - Wright, J. Talmadge; Embrick, David G.; Lukács, András (Rowman & Littlefield Publishers, 2010)
Utopic Dreams and Apocalyptic Fantasies invites us to examine critical questions about video game play, pleasure, and fantasy from a sociological perspective.